The Effect of Learning Strategies and Spatial Intelligent on the Results of Hair Style Learning - Puspa Arum, Aniesa; Ibrahim, Nurdin; Solihatin, Etin (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to find the effect of learning strategies and spatial intelligence on student learning outcomes of hairstyle courses. This research used an experimental method with a 2x2 level design using an ANOVA test for hypothesis testing. The main variable is cooperative and CTL strategies. The attribute variable is spatial intelligence, which is differentiated between high spatial and low spatial intelligence. The samples of this research were 32 students coming from two classes, which were selected randomly. Then the samples were divided into 4 cells with 8 students of each from the spatial intelligent measurement. The treatment used CTL and cooperative learning strategies to find the result. The findings are: (1) hair style learning outcomes of those who used cooperative learning are higher than those who used CTL strategies; (2) there were interactions between learning strategies and spatial intelligence on the result of hair style learning; (3) student learning outcomes who have high spatial intelligence and are taught with cooperative strategies are not higher than students who are taught with CTL strategies; and (4) hair style learning outcomes of those with low spatial intelligence who used cooperative learning are higher than those who used CTL strategies.